The case of Teatro Sociale of Sondrio for the physiognomy of theatrical audience between the nineteenth and the twentieth century (ACME, 2022)
The Teatro Sociale of Sondrio, inaugurated in 1824, between the 19th and the 20th century represents the most important theatrical centre of the whole Valtellina. Taking also in consideration the importance it holds in local history, the theatre of Sondrio can be taken as an example through which recognize, from a peculiar point of view, the evolutions italian theatre faces between the two centuries. The study of the playbills stored in the archives and that of the local newspapers allowed to analyze how and when shows were staged and how they were welcomed by Sondrio’s public and critics: on these basis, the following paper tries to offer a fisionomy of the theatrical public between the 1800s and the 1900s, a public which is a provincial one, far from that of the great cities but which, as I try to demonstrate, shares with the latest the same taste: from the researching of novelty to the passion for sentimental dramas, from the piéce bien faite to the new bourgeois dramaturgy.
Keywords: sondrio; audience; twentieth century; playbills; nineteenth century; theatre